Effectiveness of UHPC Jackets in Pier Retrofitting for Lateral Load Resistance - Zoi G. Ralli; Roberto Salazar Gonzalez; Stavroula J. Pantazopoulou (Construction Materials)
Ultra-high-performance concrete (UHPC) is a recently emerged material with exceptional durability and ductility. While widely used in bridge retrofitting, particularly to replace expansion joints and deck overlays, UHPC has seen limited use in jacketing piers for the improvement of lateral load resistance. It presents superior mechanical properties and deformation resilience, enabled by the distributed fibers and the dense microstructure, providing corrosion resistance and a maintenance-free service life. The significant tensile strength and ductility establish UHPC as an attractive resilient jacketing system for structural members. The experimental literature documents the effectiveness of this solution in enhancing the strength and ductility of the retrofitted member, whereas premature modes of failure (i.e., lap splices and shear failure in lightly reinforced piers) are moderated. A comprehensive database of tests on UHPC-jacketed piers under lateral loads was compiled for the development of practical guidelines. Various UHPC jacket configurations were evaluated, and detailed procedures were developed for their implementation in bridge pier retrofitting. These procedures include constitutive models for UHPC, confined concrete, and the strengthening of lap splices, flexure, and shear resistance. The results are supported by the database, providing a solid foundation for the broader application of UHPC in improving the lateral load resistance of bridge piers.